Musika at bagong lipunan pagbuo ng lipunang Filipino : 1972-1986 - Navarro, Raul Casantusan (Ateneo de Manila University Press, 2014)
Use of music in developing the Philippine society during martial law regime under Ferdinand Marcos' administration.